Seawater carbonate chemistry and metabolism and growth of redfish (Sebastes fasciatus) in the Gulf of St. Lawrence - Joëlle J Guitard; Denis Chabot; Caroline Senay; Dominique Robert; David Deslauriers (PANGAEA, 2025)
We quantified the effects of four acclimation temperatures (2.5, 5.0, 7.5, and 10.0 °C) and two ocean acidification scenarios (current and future) on standard and maximum metabolic rates (SMR and MMR), aerobic scope (AS), factorial aerobic scope, hypoxia tolerance (O2crit), food consumption, growth and food conversion efficiency (FCE) in redfish (Sebastes fasciatus Storer, 1854). This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were downloaded from Borealis Repository (see Source) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-11-24.